Cardiopulmonary Bypass for a Patient With Congenital Hyperinsulinemia. Issue 4 (July 2020) - Crook, Richard; Issitt, Richard
Congenital hyperinsulinism is a clinical syndrome of pancreatic β-cell dysfunction characterized by failure to suppress insulin secretion in the presence of hypoglycemia. Here, we describe the concerns, the techniques used to ameliorate these potential problems, and the outcomes for a child with this condition undergoing cardiopulmonary bypass for correction of an atrial septal defect.